Faktor-Faktor Yang Mempengaruhi Subjective Well-Being Pada Guru SD: Studi Literatur Review - Yosi Imas Kristiyana; Nurhattati Nurhattati; Kamaludin Kamaludin (Journal on Education, 2025)
There are a lot of teachers in Indonesia who still get different incomes due to their various levels or status. In Indonesia, we call it a “honorer” teacher. Having many “honorer” teachers, makes the government should be more attentive in giving the payment as it will increase the subjective well-being of teachers. This research aims to find out some factors that influence the subjective well-being of teachers. Some studies found that the level of subjective well-being in teachers in Indonesia is at a medium to high level. Subjective well-being is an important part of the teacher in doing their professional jobs. This research finds out that support from family, spirituality, collaborative environment, trust, and opportunities are some factors that could influence the subjective well-being of teachers